Therapeutic outcomes of mycophenolate mofetil and glucocorticoid in thyroid-associated ophthalmopathy patients - Li, Lan-Fang; Xue, Jun-Li; Guan, Lei; Su, Fan-Fan; Wang, Hong; Zhang, Ding-Fu (Frontiers in Endocrinology, 2023)
Objective To analyze the efficacy of mycophenolate mofetil (MMF) and glucocorticoid administration in patients with thyroid-associated ophthalmopathy (TAO). Methods Sixty patients with moderate to severe TAO treated in Jingzhou Central Hospital from January 2022 to June 2022 were selected and enrtolled in this study. The subjects were divided into experimental group (n=30) and control group (n=30) based on the random number table method. Glucocorticoid pulse therapy was provided in the control group, while MMF was given in the experimental group on the basis of Control group. Clinical activity score (CAS), quality of life (QOL), visual acuity, eyelid fissure width, intraocular pressure, and degree of exophthalmos were observed at the time of admission and at the 12th week and 24th post-treatment weeks. We compared the immune function (TRAb, IL-6, and CD4+/CD8+) of the two groups pre-treatment and 24 weeks post-treatment, and evaluated the clinical therapeutic effect. Results The clinical effective rates at 12 and 24 weeks in the experimental group were higher (73.3% and 83.3%) than those in the control group (46.7% and 60.0%) (P <0.05). After 12 weeks of treatment, patients’ CAS scores, and bilateral lid fissure width decreased and right eye visual acuity increased in the control group compared with those before treatment (P < 0.05); further, after 24 weeks of treatment, patients’ QOL scores and bilateral visual acuity increased and CAS scores, bilateral lid fissure width and proptosis decreased compared with those before treatment, and patients’ QOL scores, CAS scores and bilateral proptosis improved more than those at 12 weeks of treatment (P <0.05). Additionally, greater improvements were observed in the patients’ QOL and CAS scores, and proptosis after 24-week treatment than after 12-week treatment (P<0.05). In the experimental group, the QOL score and binocular visual acuity increased, whereas the CAS score, intraocular pressure, lid width, and proptosis decreased after 12 weeks of treatment as compared to the values of these parameters in the pre-treatment period (P < 0.05); after 24 weeks of treatment, greater improvements were established in the ocular-related indexes improved compared to the pre-treatment period and after 12 weeks of treatment (P < 0.05). After 12 weeks of treatment, the patients in the experimental group had more considerable improvements in the right visual acuity, right intraocular pressure, and left lid fissure width than the control group (P < 0.05); at 24 weeks of treatment, patients in the experimental group had greater improvements in the QOL score, bilateral visual acuity, intraocular pressure, bilateral lid fissure width, and bilateral proptosis than the control group (P < 0.05). No significant differences were found in the values of TRAb, IL-6, and CD4+/CD8+ between the two groups before treatment (P>0.05); the values of TRAb, IL-6, and CD4+/CD8+ in the experimental group was significantly lower than those before treatment and in the control group after 24weeks of treatment. (P>0.05). No statistically significant difference was observed in the incidence of liver damage and menstrual disorders between the two groups during the 24 weeks of treatment (P>0.05). Conclusion The combination of oral MMF and glucocorticoid shock therapy is an effective drug for the treatment of patients with moderately active TAO.